Penser l’agriculture dans le projet de territoire d’une ville moyenne : l’exemple de l’agglomération de Pau - Hélène Douence (Éditions en environnement VertigO, 2018)
This article is part of the renewal of studies on space systems specific to medium-sized cities, here considered from the point of view of their relations to so-called urban agriculture. The main objective of this article is to appreciate the agricultural sensitivity of the institutional city in a context of territorial and agricultural transition more or less marked according to the cities belonging to this level of the urban hierarchy. This assessment is based on a survey conducted in 2014 with 15 agents and technicians of the Agglomeration. Describing the surrounding agri-urban landscape, a first part highlights the diversity of forms of agriculture present in Pau then the rich range of concrete interactions between urban and rural-agricultural generated by certain places and involving certain social networks. The second part reflects a gap between a discourse deficit on urban agriculture and a real, but unstructured, involvement of services in actions affecting agriculture. The third part questions the local political agenda (through the "big" urban planning documents) in view of the still stammering participation of the Collectivité in an urban agricultural governance already well under way in the civil society.